The transition from development and disaster risk reduction to humanitarian relief: the case of Yemen during high‐intensity conflict. Issue 4 (1st August 2022) - Mena, Rodrigo; Hilhorst, Dorothea
Abstract : Discussions on how humanitarian aid and disaster responses can link better with development and disaster risk reduction (DRR) have occurred for decades. However, the reverse transition, from development to relief, is still poorly understood. Using the case of Yemen, this study analyses whether and how development and DRR activities adapted to the emerging humanitarian crisis when conflict escalated in the country. It concentrates on governance strategies, actors, challenges, and opportunities at the nexus of development, disaster, and humanitarian responses. Semi‐structured interviews and focus‐group discussions with aid and societal actors were conducted remotely and in Jordan. The findings show gaps in knowledge and coordination in the movement from development and DRR to relief, but also reveal spaces and opportunities to advance towards enhanced integration of action before, during, and after an emergency. This paper contributes to the literature on this nexus and critically argues for a more integrated approach to conflicts and disasters. نبذة مختصرة: كانت المناقشات حول كيفية ارتباط المساعدة الإنسانية والاستجابة للكوارث بشكل أفضل بالتنمية والحد من مخاطر الكوارث (DRR) منذ عقود. ومع ذلك ، فإن الانتقال العكسي ، من التنمية إلى الإغاثة ، لا يزال غير مفهوم بشكل جيد. باستخدام حالة اليمن ، تحلل هذه الدراسة ما إذا كانت أنشطة التنمية والحد من مخاطر الكوارث تتكيف مع الأزمة الإنسانية الناشئة عند تصاعد الصراع في البلاد و كيف . تركز الدراسة على استراتيجيات الحكم ،الجهات الفاعلة ،التحديات و الفرص في العلاقة بين التنمية والكوارث والاستجابات الإنسانية. تم إجراء المقابلات شبه المنظمة ومناقشات المجموعة المركزة مع الجهات الفاعلة في مجال المساعدة والمجتمع عن بُعد في الأردن. تظهر النتائج فجوات في المعرفة والتنسيق في الانتقال من التنمية والحد من مخاطر الكوارث إلى الإغاثة ، ولكنها تكشف أيضًا عن مساحات وفرص للتقدم نحو تكامل أفضل للعمل قبل وأثناء وبعد الأزمة. يساهم هذا المقال في الأدب المرتبط بهذه العلاقة ويدافع بشكل نقدي عن الحاجة إلى نهج أكثر تكاملاً للصراعات والكوارث. الكلمات الدالة: المساعدات الإنسانية؛ تطوير؛ الحد من مخاطر الكوارث؛ رد الفعل للكارثة؛ إسعاف ؛ صراع شديد ;اليمن 摘要: 关于人道主义援助和灾害响应如何更好地与发展和减少灾害风险联系起来的讨论已经存在了几十年。然而，人们对于从发展到救济的反向过渡仍知之甚少。本研究以也门为例，分析当该国冲突升级时，发展和减灾活动是否能够适应新出现的人道主义危机以及应该如何适应的问题。该研究侧重于发展、灾害和人道主义响应之间的关系中的治理策略、参与者、挑战和机遇。与援助和社会参与者的半结构化访谈和焦点小组讨论在约旦远程进行。调查结果显示了从发展和减灾向救济过渡的知识和协调方面所存在的差距，也揭示了在危机之前、危机期间和危机过后更好地整合行动的空间和机会。本文为有关这一关系的文献做出了贡献，并批判性地主张需要一种更综合的方法来应对冲突和灾难。 关键词： 人道援助；发展；灾难风险减少；灾害响应；救济；激烈冲突；也门